2020
DOI: 10.1002/jbt.22548
|View full text |Cite
|
Sign up to set email alerts
|

Spiraeoside protects human cardiomyocytes against high glucose‐induced injury, oxidative stress, and apoptosis by activation of PI3K/Akt/Nrf2 pathway

Abstract: The present study aimed to explore the effect of spiraeoside, an active quercetin glucoside, on diabetic cardiomyopathy in vitro. Our results showed that spiraeoside attenuated high glucose (HG)-induced reduction of cell viability and increased myocardial enzymes lactate dehydrogenase and aspartate aminotransferase in AC16 cells. Spiraeoside exerted antioxidant activity in HG-induced AC16 cells as spiraeoside inhibited reactive oxygen species and malondialdehyde production and increased activities of superoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Quercetin also improve the tricarboxylic acid cycle and respiratory chain-related enzyme activity in rats with myocardial infarction, as well as decrease the expression of biomarkers of myocardial induced oxidative stress in rats with myocardial infarction (140). In addition, quercetin protects AC16 cells from HG-induced oxidative stress by elevating p-SIRT1, endothelial NOS, and decreasing iNOS (141) through the PI3K/Akt/Nrf2 signaling pathway (142).…”
Section: Myocardial Ischemia (M/i) and Reperfusion (Mi/r)mentioning
confidence: 99%
“…Quercetin also improve the tricarboxylic acid cycle and respiratory chain-related enzyme activity in rats with myocardial infarction, as well as decrease the expression of biomarkers of myocardial induced oxidative stress in rats with myocardial infarction (140). In addition, quercetin protects AC16 cells from HG-induced oxidative stress by elevating p-SIRT1, endothelial NOS, and decreasing iNOS (141) through the PI3K/Akt/Nrf2 signaling pathway (142).…”
Section: Myocardial Ischemia (M/i) and Reperfusion (Mi/r)mentioning
confidence: 99%
“…Table 1 (Ref. [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]) provides the basic information and mechanisms of 36 flavonoids from recent studies on DCM, while Fig. 2 shows the chemical structures of the 36 flavonoids.…”
Section: Flavonoidsmentioning
confidence: 99%
“…In diabetic rats, the blocked PI3K/Akt signaling pathway results in the reduction of protein expression of eNOS, which could also regulate the level of apoptosis [ 112 ]. Liu et al showed that spiraeoside in vitro could upregulate Akt, Nrf2, HO-1, Bcl2, SOD, GPX, and CAT and downregulate caspase3, caspase7, and Bax [ 114 ]. Estrogen receptors- α 36-G protein-coupled estrogen receptor signaling complex could rapidly induce the generating of ceramide, which is necessary for signaling of ceramide-protein kinase C ζ -casein kinase 2 (CK2) [ 115 ].…”
Section: Reviewmentioning
confidence: 99%